The Influence of Management Information Systems, Competence, Motivation on Employee Performance at Pegadaian Syariah CPS (Sharia Assistant Branch) Bengkulu - Azhara Wijaya, Vanessa (JSE: Jurnal Sharia Economica, 2025)
This study aims to analyze the influence of Management Information Systems, Competence, and Motivation on Employee Performance at Pegadaian Syariah Cabang Pembantu Syariah (CPS) Bengkulu. A quantitative approach was used in this study, with data collected through questionnaires distributed to all employees, totaling 20 respondents. The research findings indicate that, partially, the Management Information System (X1) does not have a significant effect on performance, which may be due to suboptimal utilization of the system or its lack of integration with daily work needs. Conversely, Competence (X2) has a positive and significant effect, as employees with relevant skills are better able to perform their tasks effectively. Meanwhile, Motivation (X3) does not show a significant effect on performance, possibly because the type of motivation provided does not align with the employees' needs or expectations. Nevertheless, simultaneous analysis reveals that the three variables together have a significant effect on performance. This suggests that a combination of supportive information systems, appropriate competence, and suitable motivation can collectively enhance overall employee performance.